Activating Transcription Factor 4 Is Translationally Regulated by Hypoxic Stress - Blais, Jaime D. (American Society for Microbiology, 2004)
Hypoxic stress results in a rapid and sustained inhibition of protein synthesis that is at least partially mediated by eukaryotic initiation factor 2α (eIF2α) phosphorylation by the endoplasmic reticulum (ER) kinase PERK. Here we show through microarray analysis of polysome-bound RNA in aerobic and hypoxic HeLa cells that a subset of transcripts are preferentially translated during hypoxia, including activating transcription factor 4 (ATF4), an important mediator of the unfolded protein response. Changes in mRNA translation during the unfolded protein response are mediated by PERK phosphorylation of the translation initiation factor eIF2α at Ser-51. Similarly, PERK is activated and is responsible for translational regulation under hypoxic conditions, while inducing the translation of ATF4. The overexpression of a C-terminal fragment of GADD34 that constitutively dephosphorylates eIF2α was able to attenuate the phosphorylation of eIF2α and severely inhibit the induction of ATF4 in response to hypoxic stress. These studies demonstrate the essential role of ATF4 in the response to hypoxic stress, define the pathway for its induction, and reveal that GADD34, a target of ATF4 activation, negatively regulates the eIF2α-mediated inhibition of translation. Taken with the concomitant induction of additional ER-resident proteins identified by our microarray analysis, this study suggests an important integrated response between ER signaling and the cellular adaptation to hypoxic stress.